BAHASA PLESETAN DALAM ACARA INDONESIA LAWAK KLUB (ILK) DI TRANS 7 - Sari, Windy Aulia; Agustina, Agustina; Manaf, Ngusman Abdul (Jurnal Bahasa dan Sastra, 2018)
The purpose of this research was to describe the type and function of play on language in Indonesian Club Lawak (ILK) event in Trans 7. This research was a qualitative research using descriptive method. This research data are a words or combination of words which are punned in Indonesia Club Lawak (ILK) show in Trans 7. Data source in this research were Indonesian Club Lawak (ILK) event which is broadcasted on television station Trans 7. Data are analyzed by following steps : (1) transcribing the downloaded data into written language, (2) identifying the data, (3) classifying the data into plesetan types and plesetan functions, (4) analyzing the data according to the research objectives, (5) do the discussion, (6) summarizes the findings of the study, and (7) reporting the findings of the study. Keywords: puns, type and function, Indonesia Lawak Klub (ILK)